CHARACTER ANALYSIS OF STELLA IN FIVE FEET APART MOVIE - Dini Noviani Ginting; Lilis Suryani (IKIP Siliwangi, 2022)
The purpose of this study is to describe the main character in the Five Feet Apart movie. The moral messages contained among there is sincere love stories, patience in the fight against illness, close friendship relations, and others. This research is a descriptive qualitative study, where the researcher collected and analyzed data through several steps (1) the researcher watched a video that contains the Five Feet Apart movie (2) the researcher watched and observed the movie repeatedly (3) the researcher made the script of the Five Feet Apart movie as a dialog text (4) the researcher made thegroup the data in the form of dialogue that reflects the main characters in the Five Feet Apart movie (5) the researcher analyzed the dialogues that reflect the main characters of the Five Feet Apart movie in the table and (6) the researcher described and analyzed the main character in the Five Feet Apart movie. And then the researcher uses tables to measure the results of research which then concludes data relating to the main characters in the Five Feet Apart movie. Based on the results of the study found that Stella's character as the main character is humorous, full of love, friendly, steadfast, strong, smart, caring, emphatic, patient, discipline, optimistic, brave, forgiving, wise, polite, fair, obedient, and stubborn. So, Stella is the protagonists because most of her characters are good. Keywords: Movie, Character, Five Feet Apart